Pengembangan Bahan Ajar Cerpen Berbasis E-Book dengan Pendekatan Budaya Lokal dalam Meningkatkan Multiliterasi Siswa Kelas XI SMA Negeri 2 Lubuk Pakam - Anggita Nazla Munawarah; Liesna Andriany; Ali Ali (Education & Learning, 2025)
This research and development (R&D) study was conducted to design and evaluate an interactive e-book for short story learning that integrates local cultural values as a means to enhance the multiliteracy competencies of eleventh-grade students at SMA Negeri 2 Lubuk Pakam. The study addressed the problem of limited engaging and culturally relevant learning media for short story instruction by developing an innovative digital teaching material. The development followed the ADDIE model, which consists of five systematic stages: Analyse, Design, Develop, Implement, and Evaluate. Data were collected through Likert-scale questionnaires administered to two content experts and two media experts, and then analysed using descriptive quantitative methods. The validation results showed that the first content expert rated the e-book at 74.6% (valid and feasible), while the second content expert rated it at 76.6% (valid and feasible). The media experts evaluated the product with higher ratings, namely 91.3% (very valid and highly feasible) and 81.3% (valid and feasible). These findings indicate that the developed e-book meets educational quality standards, is feasible for classroom application, and provides a novel contribution by embedding local cultural values into short story learning to support students’ multiliteracy competencies.